Sistem Informasi Persediaan Perlengkapan Alat Alat Isi Ulang Air Minum Pada Toko Gun CS - Darmuji Darmuji; Christo Randzio Simbolon (Journal of Applied Accounting and Business, 2021)
Gun cs shop is a company engaged in the sale of refill equipment. The process of data collection of incoming goods and goods out of stock inventory when searching for goods data is still using the manual method. With this, in order to make it easier, it is recommended to use an inventory information system. The purpose of this inventory system is to overcome the system that is currently running at the gun cs shop as well as a solution so that the store can manage inventory data more quickly. The result of this research is to produce a web-based inventory information system with the LIFO FIFO and Avarage method which provides convenience in providing information on inventory data through incoming and outgoing goods using data flow diagrams, DFD, ERD and MySQL for data processing.